INOVASI METODE BERCERITA DENGAN WAYANG KARDUS UNTUK MENINGKATKAN KEMAMPUAN BERBICARA DAN PERCAYA DIRI ANAK - Wawan Gunawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of the storytelling method using cardboard puppets and learning motivation on the speaking ability and self-confidence of kindergarten children. This study used a quantitative design with an experimental approach, where the research subjects were kindergarten children who were divided into two groups: an experimental group using the storytelling method using cardboard puppets and a control group using the lecture method. This research method used measurement instruments in the form of a speaking ability test and a scale for measuring children's self-confidence. Data were collected through observation, interviews with teachers, and questionnaires filled out by parents related to the level of children's learning motivation. Data analysis was carried out using descriptive and inferential statistical techniques with the help of SPSS 27 software for hypothesis testing. The results showed that the storytelling method using cardboard puppets had a significant effect on the speaking ability and self-confidence of kindergarten children. This method proved to be more effective than the lecture method. In addition, children's learning motivation also played an important role, where children with high learning motivation showed greater improvements in speaking ability and self-confidence. The interaction between the storytelling method using cardboard puppets and learning motivation showed that these two factors were mutually reinforcing, providing a greater impact on the development of both variables. Based on the research findings, it is recommended that teachers select and integrate interactive methods, such as storytelling using cardboard puppets, especially for children with high learning motivation. Further research is also recommended to investigate the influence of children's emotional factors, such as anxiety or fear, which may affect their speaking skills and self-confidence.